Intravenous tirofiban in acute ischemic stroke patients not receiving reperfusion treatments: a systematic review and meta-analysis of randomized controlled trials - Alqurashi, Shatha; Alqahtani, Mohammed S; Albeladi, Shahad Mohammed; Almahdawi, Saleha; Danish, Hala; Alshaikh, Hatoon; Alkhiri, Ahmed; Alkawi, Ammar; Al-Ajlan, Fahad S; Alhazzani, Adel (Frontiers in Neurology, 2025)
BackgroundReperfusion treatments with intravenous thrombolysis and endovascular thrombectomy after acute ischemic stroke (AIS) can improve patients’ outcomes significantly. Yet, a substantial portion of patients miss the opportunity to receive reperfusion treatments. In this study, we aimed to assess the role of intravenous tirofiban in this specific population.MethodsA search was performed in Embase, Cochrane Central Register of Controlled Trials, Medline, and Web of Science databases from inception until August 2024. The random-effects model was used to calculate odds ratios (ORs) with their corresponding 95% confidence intervals (CIs). Efficacy endpoints included excellent (modified Rankin scale of 0–1) and good (modified Rankin scale of 0–2) functional outcomes at 90 days. Safety outcomes included symptomatic intracerebral hemorrhage (sICH), any ICH, and 90-day mortality.ResultsFour randomized clinical trials, including a total of 1,199 patients, were included. Of these, 599 patients (50%) received tirofiban. The meta-analysis demonstrated that tirofiban was associated with significantly higher rates of both excellent (OR 1.63 [95% CI, 1.24–2.13]; I2 = 0) and good (OR 1.65 [95% CI, 1.19–2.29]; I2 = 0) functional outcomes at 90 days. No significant differences were observed in sICH, any ICH, or 90-days mortality.ConclusionTreatment with intravenous tirofiban can be beneficial without increased risk in patients with AIS who are not eligible for reperfusion treatment. Further studies are still needed to validate the generalizability of these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024590097, CRD42024590097.